An appraisal of the doctrines of exhaustion, ripeness and locus standi as means to preventing frivolous action against administrative decisions in Nigeria (2015)
Judicial review of administrative decisions is a great weapon in the hand of judges to control administrative excesses and abuse of power. Over the years, several doctrines were developed to aid the court in the determination of whether to intervene in administrative proceedings or to tarry until a decision is reached. To checkmate abuse of power by administrative agency or inferior courts, doctrines like prohibition, certiorari, mandamus, ultravires, declaration, habeascorpus are ready tools in the hands of the judiciary. Conversely, to prevent frivolous actions from citizenry, the doctrines of exhaustion, ripeness, and locusstandi were evolved. Judicial intervention may come either at the preenforcement or post-enforcement stages. The doctrines of exhaustion, ripeness and locusstandi are pre-enforcement remedies, while doctrines like certiorari, declaration and ultravires operate' as post-enforcement remedies. This paper seeks to appraise pre-enforcement remedies. Case law is extensively used to illustrate their import.